Road safety survey 2007 - Swedish Road Administration (Swedish Transport Administration, 2013)
This is the 26th study in a series of annual surveys on road safety conducted since 1981. The study is conducted by Statistics Sweden on behalf of the the Swedish Road Administration and aims to identify and analyse traffic safety statistics.

The study is is done by a questionnaire directed to a stratified sample of the population. The study from 2007 had a 61,6 percent response rate and a sample of 8 995 randomly selected people aged between 15 and 84 years.

The questions in the study include, for example, traffic behaviour and traffic patterns; attitudes to road safety and traffic rules, the relation between alcohol and traffic and child safety in traffic. Both motor traffic, bicycle and foot traffic is concerned. A total of 25 questions are used, including descriptive questions, estimation questions and attitude questions.

Purpose:

The aims of the study is to identify and analyse traffic safety statistics.

Detta är den 26:e studien i en serie av årliga undersökningar om trafiksäkerhet som genomförts sedan 1981, med syfte att ta fram och analysera trafiksäkerhetsstatistik. 2007 års studie har har utförts av Statistiska centralbyrån på uppdrag av dåvarande Vägverket. Sedan 2010 är det Trafikverket som ansvarar för studien.

Undersökningen genomförs genom ett frågeformulär riktad till ett stratifierat urval av Sveriges befolkning. Svarsfrekvensen var 61,6 procent för urvalet 8 995 slumpmässigt utvalda personer i åldrarna 15 till 84 år.

Frågorna i studien behandlar bland annat trafikbeteende och trafikvanor, både hos sig själv och andra, inställning till trafiksäkerhet och trafikregler, relationen mellan alkohol och trafik samt barns säkerhet i trafiken. Både motortrafik, cykel och gångtrafik berörs. Totalt används 25 stycken frågor som består bland annat av beskrivande frågor, skattningsfrågor och attitydfrågor.

Syfte:

Syftet med studien är att ta fram och analysera trafiksäkerhetsstatistik.
Trafiksäkerhetsenkäten 2007
TS-enkäten 2007
Keywords: drinking behaviour; alkoholvanor; road traffic; vägtrafik; speed limits; fartgräns; protective headwear; skyddshjälmar; road accidents; trafikolyckor; road safety; trafiksäkerhet; cyclists; cyklister; child safety; barnsäkerhet; traffic regulations; trafikbestämmelse; bicycles; cyklar; breathalyser testing; alkoholtest; traffic; trafik; safety equipment; säkerhetsutrustning; road users; vägtrafikanter; velocity; hastighet; vehicle restraint systems; bilens inre säkerhet; traffic offences; trafikförseelse; Legislation and legal systems; Lagstiftning och rättssystem; Children; Barn; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap